Sculptures of Nayikas inside the sanctum of Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
Inside the sanctum of the temple are beautiful sculptures of nayikas on the wall, while at the centre of the principal/back wall is placed a colossal image of Parvati in penance or the pancagni tapa. Interestingly, their names are scribed in the kuṭila script of the 10th century CE. The inscribed epithet calls her Vikata, a possible explanation for this unusual name would be Gauri treading the Vikata-marga by performing penance. This epithet also appears in the Harsha stone inscription of VS 1030. Shiva, who occupies a central place in the sanctum in the form of linga placed on yoni, is coupled with the representation of Shakti on the surrounding walls inside the sanctum. A four-armed Parvati is depicted performing the penance of the pancagni-tapa, visually represented with fires on either side. She stands erect on an iguana, earning the label Godhasana Gauri. Flanking her are two standing and two sitting female attendants on either side.